A STUDY TO ASSESS THE KNOWLEDGE OF RADIO IMAGING TECHNOLOGY AMONG STUDENTS TOWARDS HANDLING THE RADIOGRAPHIC MODALITIES - Chauhan, Tarun; Kumar Mann, Ashish; Kumar, Vaibhav (International Journal For Research In Health Sciences And Nursing, 2023)
Background: The main focus of the curriculum of radio imaging technology course is to spread knowledge, skills, attitude required for the practice. By communication skills students can practice more with volunteer patients. The students in radiography include the subjects such as Anatomy and physiology, radiographic equipment’s, radiation protection, radiography imaging techniques etc. Knowledge estimation may be beneficial for finding possible gap in an organization and publicize actual weakness and drawbacks. Present report on knowledge estimation takes preference over analyze specific qualified professional that are completely resolve by technology. Objective: The aim of this study is to assess handling and care of radiographic modalities and knowledge of students on different modalities. Methods: 94 samples data were collected prospectively and mean, average and percentage stats are used. Result: Out of 94 Samples, the male population was 49 (52.1%) and female 46 (48.9%). They were divided into four categories on the basis of their class standards in which two were (BSc 2 nd and 3rd year) and other two were (MSc. 1st year and MSc. Final year students). Finding shows that BSc. 3rd year has highest knowledge on radiographic modalities i.e. 18.54% and BSc. 2nd year with least knowledge on radiographic modalities i.e. 16.80%. Conclusion: The study concludes that knowledge related to radiographic modalities, handling and care of radiographic modalities must be known to everyone in terms of safety and precaution while working in the radiology department. Safety standards were maintained and guidelines were made along with how to use different modalities and how to handle them with care. Class should be taken at regular interval to check the knowledge of radiographers and staff working in the radiology department so that in case of emergency that can handle and safe both the patient and machine form damage.